A Levallois point embedded in the vertebra of a wild ass (Equus africanus : hafting, projectiles and Mousterian hunting weapons - Boëda, Eric
The hunting methods of the Neanderthals are rarely evident in detail in the archaeological record. Here, the rare and important discovery of a fragment of broken Levallois point, embedded in the neck-bones of a wild ass, provokes plenty of discussion of the methods of hafting and killing game in the Middle Palaeolithic of Syria.